Distortionary Domestic Taxation and Pareto-Efficient International Trade - Jeremy Edwards; Ronnie Schöb (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper characterises the domestic tax systems which yield Pareto-efficient outcomes for a two-country world economy in which each country uses distortionary taxes. Such outcomes are compared with the Nash equilibria of the world economy when each country uses its domestic tax system to influence ist terms of trade. In such circumstances, the implementation of domestic tax systems which achieve a globally Pareto-efficient outcome as a Nash equilibrium will be very difficult, for two main reasons: the ability of countries to use tax policy with respect to non-traded goods for protection, and the fact that Pareto-efficient tax structures depend on countries distributional judgements, which are hard to measure objectively.
Keywords: 330